Move theorem of the short-cut statistic procedure - Petronaitis, Darius; Aksomaitis, Algimantas (Lietuvos matematikos rinkinys, 2002)
The limit distribution functions are obtained for the extremes difference and extremes arithmetic average with random indices under nonrandom normalization.